Kebutaan Akibat Kelainan Mitokondria : Gejala, Diagnosis, dan Tata Laksana Suportif - Ratna Sitompul (Majalah Oftalmologi Indonesia, 2016)
Mitochondria is an important organelle in the cell acting as its powerhouse. Damage in the mitochondria leads to cell death thus it is crucial to organs utilizing plenty of energy such as the eyes. Mitochondrial disease in the eye can be primary or secondary. Primary mitochondrial diseases of the eye include dominant optic atrophy, leber hereditary optic neuropathy, chronic progressive external ophthalmoplegia, and retinitis pigmentosa. Secondary mitochondrial eye diseases include diabetic retinopathy, age-macular degeneration and glaucoma. Mitochondrial damage can also trigger growth of ocular neoplasm (retinoblastoma and uveal melanoma) are also part of mitochondrial eye diseases. However, it is still a challenge to diagnose mitochondrial eye diseases. Methods that can be used are genetic sequencing, radiological examinations to look for other syndromic signs, as well as biochemistry and histochemistry assays. Definitive therapy for mitochondrial eye diseases are still under research and to date the management is supportive in the form of food supplementation. Keywords: primary mitochondrial diseases, secondary mitochondrial disease, mtDNA.ROS, ocular tumour